Short-term prognostic analysis of patients with systemic lupus erythematosus co-infection and comparison of mNGS and conventional microbiological test results - Zhao, Xi; Duan, Ming-Xuan; Lu, Yan-Yu; Bai, Lin-Peng; Zhao, Xiao-Yan (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives Infection is one of the major causes of morbidity and mortality in patients with systemic lupus erythematosus (SLE), and as a new diagnostic technique, metagenomic next-generation sequencing (mNGS) is increasingly used for the pathogenetic detection of co-infected SLE patients. However, conventional microbiological testing (CMT) is still the gold standard for pathogenic diagnosis, and the specific diagnostic efficacy of mNGS versus CMT in such patients is not known. In addition, there are few studies on the short-term prognosis of co-infected SLE patients. Methods This study retrospectively included 58 SLE patients with co-infection admitted to the First Affiliated Hospital of Zhengzhou University from October 2020 to August 2022. Patients were divided into a survivors (n=27) and a non-survivors (n=31) according to their discharge status. Baseline characteristics and etiological data were collected and statistically analyzed for all patients during their hospitalization. The sequential organ failure assessment (SOFA) score, acute physiology and chronic health evaluation (APACHE) II and systemic lupus erythematosus disease activity index (SLEDAI) were calculated for each patient to assess the predictive ability of the 3 scores on the short-term prognosis of SLE patients. The mNGS and CMT culture results were also compared to clarify the flora characteristics of patients with SLE infection. Results More patients in the non-survivors had renal impairment, neurological manifestations, multiplasmatic cavity effusion and gastrointestinal manifestations compared to the survivors (p < 0.05). The SOFA score, APACHE II and SLEDAI were significantly higher in the non-survivors than in the survivors (p < 0.01). There were also significant differences between the two groups in several tests such as hemoglobin, platelets, albumin, total bilirubin, C-reactive protein (CRP), procalcitonin (PCT), and complement C3 (p < 0.05). In addition, the absolute values of T lymphocytes, CD4+ T cells and CD8+ T cells were smaller in the non-survivors than in the survivors (p < 0.05). The most common type of infection in this study was pulmonary infection, followed by bloodstream infection. mNGS and CMT positivity rates were not significantly different among patients in the non-survivors, but were significantly different among patients in the survivors (p=0.029). In-hospital survival of patients with SLE infection could be predicted based on the SOFA score in relation to 6. For patients with SOFA <6, we recommend earlier mNGS testing to identify the pathogen and improve patient prognosis. Conclusions For SLE patients with co-infection, in-hospital survival can be predicted based on SOFA score. For patients with SOFA <6, advising them to complete mNGS testing as early as possible may improve the prognosis to some extent.